Perancangan Oven Pengering Mie Berkapasitas 15 kg/jam untuk Mendukung Produktivitas PT. Star Umroh Food - Muhammad Idris; Bobby Umroh; Uun Novalia Harahap; Iswandi Iswandi; Indra Hermawan; Mahliza Nasution; Darianto Darianto; Tino Hermanto; Yetti Meuthia Hasibuan (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
Noodle drying at PT. Star Umroh Food still uses sunlight, so it depends on the weather, the temperature is not controlled, the productivity is low, and the level of product dryness is not uniform. This community service activity aims to design a gas-fueled dryer oven with a capacity of 15 kg/hour with forced convection. The methods are surveys, needs analysis, 2D and 3D design, specification analysis and evaluation. The results of the design of the oven with dimensions of 170 × 300 × 180 cm, a working temperature of 70 °C, and an estimated LPG consumption of 0.6 kg/hour. The prediction of increasing productivity and producing more uniform drying.